2019
DOI: 10.1371/journal.pone.0222039
|View full text |Cite
|
Sign up to set email alerts
|

What are the characteristics that lead physicians to perceive an ICU stay as non-beneficial for the patient?

Abstract: Purpose We sought to describe the characteristics that lead physicians to perceive a stay in the intensive care unit (ICU) as being non-beneficial for the patient. Materials and methods In the first step, we used a multidisciplinary focus group to define the characteristics that lead physicians to consider a stay in the ICU as non-beneficial for the patient. In the second step, we assessed the proportion of admissions that would be perceived by the ICU physicians as non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Indeed, the ICU physician is then in the awkward position of choosing between loss-of-opportunity for the patient if admission is refused, or alternatively, delivery of care that may later be deemed disproportionately burdensome [ 40 , 41 ] or even futile [ 42 ]. This can result in ICU admissions that are judged to have been non-beneficial [ 25 ]. The findings of this study plead in favour of enhanced collaboration between intensivists and referring specialists when there is debate about a potential ICU admission, especially if the question is being considered before any acute organ failure has occurred [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the ICU physician is then in the awkward position of choosing between loss-of-opportunity for the patient if admission is refused, or alternatively, delivery of care that may later be deemed disproportionately burdensome [ 40 , 41 ] or even futile [ 42 ]. This can result in ICU admissions that are judged to have been non-beneficial [ 25 ]. The findings of this study plead in favour of enhanced collaboration between intensivists and referring specialists when there is debate about a potential ICU admission, especially if the question is being considered before any acute organ failure has occurred [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is incumbent on ICU physicians to offer care that will provide the patient with a level of therapeutic engagement commensurate with that patient’s healthcare goals, personal desires and values, and with an acceptable anticipated quality of life after discharge from the ICU [ 22 , 23 ]. However, this balance can be difficult to achieve, especially in emergency situations, with a trade-off often occurring between the risk of loss of opportunity if ICU admission is refused, and the risk of unreasonable therapeutic obstinacy if the patient’s stay in the ICU is ultimately non-beneficial [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent prospective, multicentre centre study in France that included 1075 patients [ 30 ] found that 14.4% of admissions to the ICU were felt to be inappropriate by the ICU physicians. The fact that ICU care or an ICU stay could be considered inappropriate should prompt us to think about ways to limit, or even avoid such situations, which can have nothing but negative consequences for the patient, the family and the healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
“…The 4 domains addressed by the questionnaire, as well as the individual questions in each domain were developed based on a focus group of 10 physicians from university and non-academic hospitals, according to the methodology previously described elsewhere [ 12 ]. Briefly, 1 clinician (JPQ) and 1 sociologist (NMB) led the focus group discussions using open-ended questions to prompt the participants to envisage all the aspects that contribute to an ICU stay being considered as inappropriate or non-beneficial.…”
Section: Methodsmentioning
confidence: 99%
“…In one North-American study, 31% of patients who died in hospital were admitted to the ICU, despite the fact that they had clearly expressed a desire to receive comfort care only, and among these, 14% had received one or more life-sustaining therapies [ 11 ]. Recently, a prospective, multicentre study from France involving 4 centres showed that up to 22% of ICU stays could be deemed “non-beneficial” [ 12 ]. The authors showed that in approximately one quarter of “non-beneficial” ICU admissions, the patient had not wanted to be admitted to the ICU.…”
Section: Introductionmentioning
confidence: 99%